Antioxidant, Cytotoxic, and Insulinotropic Activities of Several Leaves Extracts of Medicinal Plants - Amelia Marzanti; Riska Widya Aprianti; Silmi Mariya; Rachmitasari Noviana; Eti Rohaeti; Irma Herawati Suparto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The prevalence of diabetes mellitus and cancer is increasing; thus, research into efficient treatments utilizing active compounds derived from medicinal plants has focused on these diseases. Through the agro maritime 4.0 approach, medicinal plants are explored in the archipelago of Indonesia, particularly on Tinjil Island, Banten Province. The medicinal plants identified on the island include Morinda citrifolia, Terminalia catappa, and Gnetum gnemon. Therefore, this study aimed to evaluate the in vitro of aqueous extracts of leaves of those three plant species. All aqueous extracts were analyzed for total phenolic content and further tested for antioxidant activity using the DPPH method (2,2-diphenyl-1-picrylhydrazyl), MTT cytotoxic activity (3-[4,5-dimethylthiazole-2-yl]-2- 5-diphenyl-tetrazolium-bromide) in MCF-7- (ATCC HTB 22) and Burkitt’s Lymphoma Raji (ATCC CCL 86) cells, and insulinotropic activity in pancreatic BRIN BD11 cells. The results showed that the total phenolic content of T. catappa was significantly higher (9.21 ± 2.49 mg GAE/g extract sample) compared to M. citrifolia (3.00 ± 0.35 mg GAE/g) and G. gnemon (7.47 ± 0.33 mg GAE/g). Compared to the other two extracts, T. catappa extract has the best DPPH antioxidant activity of IC50 7.44 ± 0.77 µg/mL (p<0.05). MTT cytotoxic activity in all samples did not inhibit the proliferation of Raji cells but did the proliferation of MCF-7 cells. The IC50 for the best cytotoxic activity was shown in M. citrifolia (8.06 µg/mL). T. catappa triggered insulin secretion at 62.5 µg/mL with the highest insulin concentration (54.55 mg/mL). The aqueous extract of T. catappa leaves shows potential as an antioxidant and insulinotropic agent, while M. citrifolia leaves have a cytotoxic effect with anticancer potential.